Psychological Profile and Competitive Performance in Group Aesthetic Gymnastics - Celia Armada Martínez; Francisco Cavas-García; Arturo Díaz-Suárez; Alfonso Martínez-Moreno (Frontiers Media S.A., 2021)
The objective of the research was to evaluate the perceptions about the psychological variables of cohesion and motivational climate that AGG gymnasts have about the context created by the coaches in their teams and to analyze in the different categories the optimism and competitive anxiety they face in competitive situations. In an attempt to clarify the psychosocial training patterns in this sport and the influence they have on the well-being of its practitioners, competitive anxiety, motivational climate, team cohesion and level of optimism were taken as dependent variables. The sample was made up of 98 national and international junior and senior athletes in the aesthetic gymnastics group aged 13 to 27 (M = 17.1; SD = 2.8). The Perceived Motivational Climate in Sport Questionnaire for motivational climate, the Sport Anxiety Scale-2 for competitive anxiety, the Group Environment Questionnaire for cohesion and the Revised Life Orientation Test for optimism were used in the evaluation. The results obtained show a positive and statistically significant correlation between anxiety and ego involvement, while, for task involvement, high levels of cohesion are associated with high levels of optimism (p = 0.005). In conclusion, the data confirm that high levels of cohesion are associated with high levels of optimism, in addition high scores on task involvement show high scores on cohesion and optimism, however high scores on ego involvement are associated with low scores on cohesion and optimism.